Investigating the potential impact of wind farms on Lake Erie. Issue 198 (March 2020) - Afsharian, Soudeh; Taylor, Peter A.; Momayez, Ladan
Abstract: Power generation is a leading cause of air pollution and major source of global warming emissions. Renewable energy resources, like wind and solar power, generate electricity with little to no global warming emissions and are reliable, affordable and beneficial for health, economy and climate. There are two sectors in wind energy: offshore and onshore. Offshore wind speeds are faster and steadier and coastal areas often exhibit a high energy demand. Offshore wind farms are coming to the Great Lakes. We therefore investigate the potential impact of wind farms on Lake Erie's dynamic and thermal structure using the COHERENS (a Coupled Hydrodynamical-Ecological model for Regional and Shelf Seas) and simulate a large wind farm with 432 offshore turbines located in the shallow southern waters of the central basin. The simulation is run twice to compare physical parameters such as temperature and circulation pattern and velocity results in the absence and presence of a large wind farm. In the case of no wind farm, model results are validated with data from buoys located in Lake Erie, while with the wind farm, the results show that the central basin is impacted by the wind turbines. This occurs because the reduced wind speed and stress leads to less mixing, lower current speeds and higher surface water temperature. There is no significant impact, however, in the eastern and western basins. This research examines Lake Erie, since this lake has a high potential for offshore wind turbine installation due to its proximity to population centers and its shallow depth. Key Points: Large turbines in wind farms reduce wind speeds. Lower wind speed leads to shallower water mixed layer and stronger thermocline. Impacts are stronger on deeper waters.